Analisis Ekspor Minyak Kelapa Sawit (CPO) Indonesia Ke Sepuluh Negara Tujuan Utama Tahun 2008-2020 - Juni Karlina, Catur; Sri WInarti, Asih; Sodik, Jamzani (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Indonesia is the largest palm oil producer in the world as well as the world’s largest CPO exporter. However, Indonesia has not been able to become a peg for CPO prices and in 2020 there was a decrease in CPO export volume due to pandemic Covid-19. This study aims to: (1) analyzing the effect of Gross Domestic Product of the destination country on Indonesian palm oil (CPO) exports in 2008-2020. (2) analyzing the effect of Economic Distance on Indonesian palm oil (CPO) exports in 2008-2020. (3) Analyzing the effect of Riil Exchange Rate on Indonesian palm oil (CPO) exports in 2008-2020. (4) Analyzing the effect of palm oil export prices on Indonesian palm oil (CPO) exports in 2008-2020. This study uses secondary data related to palm oil sources from BPS, Bappepti, BI, BPDPKS, World Bank, and other related sources. The analytical tool used in this research is panel data regression analysis (pooled data) with Gravity Model. Based on the result of the analysis, it is know that Gross Domestic Product (GDP) of export destination countries, Economic Distance, and Riil Exchange Rate has positive and significant effect of on CPO exports. While CPO Export Price variables have a negative dan significant effect on CPO exports.